(3GdJYdje ddQjGOI aj GdOhd GdYQHjI (B: (3eTQhY eTJQc Hjf GdjhfSch heDSSI SJQGJ QjGd GdHQjWGfjI; Gdechf GdKGfj(B: (3GdJbQjQ GdEbdjej GdJhdjajs - (3GdcShGfj, YHjQs ((3HjQhJs (3GdjhfSch (B/ (3GdTQGcI aj GdJYdje ddQjGOIs, 2013)
(3jbqOe gPG GdJbQjQ JUqhQkG TehdjkqG Yf EfLGRGJ GdOhd GdYQHjI GdeTGQcI aj eTQhY GdJYdje ddQjGOI(B- (3Gdechf GdKGfj (B(2011 - 2012)(3, hGdOQhS GdeSJaGOI ef eQGMd JfajP GdeTQhY hJbOje GdGSJfJGLGJ hGdJhUjGJ, ddeSGgeI aj QaY GdhYj HefLRGJ heSGgeGJ GdOhd GdYQHjI GdeTGQcI hJYRjRgG, hdjJSfi ddOhd GdYQHjI GdCNQi GdQGZHI aj OeL GdJYdje ddQjGOI aj fXGegG GdJYdjej GdGSJaGOI ef gPg GdNHQGJ hGdJLGQH, hJTLjY aQU GdJYGhf Hjf Ohd GdefWbI(B. (3GTJedJ GdefgLjI GdeSJNOeI dEYOGO gPG GdJbQjQ Ydi eQGLYI GdJbGQjQ GdhWfjI ddechf GdKGfj (B(2011 - 2012) (3dcd ef (B((3GdCQOf, SdWfI YeGf, dHfGf, GdeZQH(B)(3, hGdESJfGO Edi eG LGA aj JbGQjQ hChQGb Yed GdOhd GdYQHjI GdeTGQcI aj hQTI GdYed GdEbdjejI Mhd GdJYdje ddQjGOI aj GdOhd GdYQHjI (B((3GdefGeI (B- (3GdHMQjf (B10-12 (3cGfhf Ghd (B2012)(3, GdEWdGY Ydi GdeHGOQGJ hGdHQGeL PGJ GdYdGbI HGdQjGOI GdefaPI Ydi GdeSJhjGJ GdhWfjI hGdEbdjejI hGdOhdjI, EVGaI Edi eLehYI ef GdeQGLY hGdOQGSGJ JhGaQJ ef bHd ecJH GdjhfSch(B. (3de JXgQ aj JLGQH GdOhd GdCQHY bVGjG GdfhY GdGLJeGYj HTcd hGVM aj eLGd GdJYdje ddQjGOI, Hd cGfJ GdJhLgGJ LejYgG ddLfSjf HdG JMjR(B. (3dbO JecfJ GdHdOGf GdeTGQcI ef JMbjb GdfLGM aj LhGfH YOI ddeTQhY, MjK JecfJ ef hVY GdJYdje ddQjGOI hOhQgG aj GdJfejI GdGbJUGOjI hGdeLJeYjI, hJMOjO GdeYfjjf hGdeSJajOjf ef GdQjGOI, hef Ke EYOGO eSJdReGJ OeL GdQjGOI aj GdJYdje ef efGgL hCOdI eYdejf, hOhQGJ JOQjHjI, hehGbY EdcJQhfjI eJNUUI(B.s
(3GdfhY (B: (3JbQjQs
Keywords: Leadership; Leadership Arab Countries; Les pays Arabes; (3GdbjGOI GdOhd GdYQHjIs